User Experience Evaluation of Online Registration System at RSUP Surakarta Using the UEQ Method - Guruh Anang Setyadi; Aries Widiyoko (International Journal of Public Health, 2025)
The rapid advancement of digital technology has transformed healthcare services, including the implementation of online registration systems in hospitals. RSUP Surakarta has operated an online patient registration system since 2021 to reduce wait times and improve service efficiency. However, no formal evaluation has been conducted from the user experience (UX) perspective. This study aims to evaluate the UX of RSUP Surakarta’s online registration system using the User Experience Questionnaire (UEQ) method. A descriptive quantitative approach was employed with accidental sampling involving 100 respondents who had used the system in 2024. The UEQ measured six aspects: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. Results revealed that all aspects scored positively, with Attractiveness (1.920) and Dependability (1.810) reaching the “Excellent” benchmark. Perspicuity (1.863) and Efficiency (1.868) also showed strong scores, while Stimulation (1.693) and Novelty (1.130) scored lower in the “Good” category. These findings suggest that although the system is well-received, improvements are necessary in terms of user engagement and innovation. Enhancing the user interface and enriching system features are recommended to optimize user satisfaction and ensure alignment with patient-centered service standards. This study contributes to digital service evaluation practices in public healthcare by providing empirical insights into user perceptions and expectations.